Bacteriophages in Therapeutics - Bhonchal Bhardwaj, Sonia (IntechOpen, 2021)
As pathogenic bacteria continue to develop multi-drug resistance, antibacterial treatment strategies such as bacteriophages are needed. This book serves as a brief yet exhaustive guide to the biology of bacteriophages and their role in health and disease. It is a useful resource for microbiologists, bacteriophage researchers, clinicians providing bacteriophage therapy, and dental and medical students.